2007
DOI: 10.1590/s1516-635x2007000200006
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine decarboxylase expression in the small intestine of broilers submitted to feed restriction and glutamine supplementation

Abstract: Six hundred and forty one-day-old Cobb male broilers were used to evaluate ornithine decarboxylase (ODC) expression in the mucosa of the small intestine. Birds were submitted to early feed restriction from 7 to 14 days of age. The provided feed was supplemented with glutamine. A completely randomized design with a 2 x 2 factorial arrangement was used (with or without glutamine, with or without feed restriction). Restricted-fed birds were fed at 30% the amount of the ad libitum fed group from 7 to 14 days of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In contrast to the results in cows and calves, the findings in pigs indicated that feeding 0.8-4% Gln in diet had beneficial effects in alleviating growth depression of E. coli K88 +challenged pigs (Yi et al, 2002;Yi et al, 2005b), enhancing body weight gain and feed efficiency of weaned piglets (Lackeyram et al, 2001;Wang et al, 2008). In poultry, supplementing the diet with 1% Gln improved (p<0.05) the weight gain and feed efficiency of broilers (Yi et al, 2001), and increased the ornithine decarboxylase (ODC) expression (Fischer da Silva et al, 2007b). Bartell et al (2007) further indicated that the addition of 1% Gln to the diet of broiler chicks improved the weight gain, 4% Gln in diet or water depressed the growth performance.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast to the results in cows and calves, the findings in pigs indicated that feeding 0.8-4% Gln in diet had beneficial effects in alleviating growth depression of E. coli K88 +challenged pigs (Yi et al, 2002;Yi et al, 2005b), enhancing body weight gain and feed efficiency of weaned piglets (Lackeyram et al, 2001;Wang et al, 2008). In poultry, supplementing the diet with 1% Gln improved (p<0.05) the weight gain and feed efficiency of broilers (Yi et al, 2001), and increased the ornithine decarboxylase (ODC) expression (Fischer da Silva et al, 2007b). Bartell et al (2007) further indicated that the addition of 1% Gln to the diet of broiler chicks improved the weight gain, 4% Gln in diet or water depressed the growth performance.…”
Section: Discussionmentioning
confidence: 72%
“…The benefit of Gln supplementation has been associated with a better development of the gastrointestinal tract. Chickens supplemented with 1% Gln have longer VH and deeper CH (Fischer da Silva et al, 2007;Murakami et al, 2007;Soltan, 2009). The increased VH and CD due to AG supplementation is an important finding because the gastrointestinal tract is particularly sensitive to environmental stressors, which may induce various changes including decreased integrity of the intestinal epithelium (Meddings and Swain, 2000).…”
Section: Glutamine and Glutamic Acid In Broilersmentioning
confidence: 99%
“…Glutamine (Gln) is an abundant amino acid in the body and is regarded as a conditionally essential nutrient in animals under stress conditions, such as infection, injury, high temperature and weaning (Murakami et al, 2007;Souba et al, 1990;Wu et al, 1995;Soltan, 2009;Dai et al, 2009;Fischer da Silva et al, 2007;Bartell and Batal, 2007). Dietary supplementation of Gln has been reported to play an important role in preserving gut integrity in rodents (Larson et al, 2007) and pigs (Wu et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Arg is, indirectly, the precursor of putrescine, spermidine, and spermine through L-ornithine and agmatine. Putrescine can be formed virtually in all tissues, including intestinal cells of poultry, via Arg-ornithine-putrescine pathway that is catalyzed by the enzymes arginase and ornithine decarboxylase ( Tabor and Tabor, 1984 ; Fischer da Silva et al., 2007 ). Alternatively, putrescine can be synthesized in the Arg–agmatine—putrescine pathway, which includes the enzymes arginine decarboxylase and agmatinase ( Horyn et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%